2020
DOI: 10.1155/2020/3970860
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Aging: Understanding the Complex Relationship among Aging, Free Radicals, and GSH

Abstract: N-aryl maleimides can undergo a 1,4-Michael-type addition reaction with reduced glutathione (GSH), leading to a decreased concentration of GSH and an increased concentration of free radicals (FRs) in cells. GSH is a critical scavenging molecule responsible for protecting cells from oxidation and for maintaining redox homeostasis. N-aryl maleimides disturb redox homeostasis in cells because they scavenge thiol-containing molecules, especially GSH. This study aimed at measuring the concentrations of GSH and FRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…On the other hand, one could also argue that these differences are once again due to the age difference observed between participants, or the epiphenomenon of an adaptation following prolonged exposure to hypoxic conditions. Previous research on animals has suggested an age-related decrease in the GSH content of several tissues, paired with an increase in GSH oxidation to glutathione disulfide (GSSG) [ 48 , 49 , 50 ]. Thus, a decrease in GSH would have been expected in the older, expert pilots, whereas instead, an increment is noted post-flight simulation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one could also argue that these differences are once again due to the age difference observed between participants, or the epiphenomenon of an adaptation following prolonged exposure to hypoxic conditions. Previous research on animals has suggested an age-related decrease in the GSH content of several tissues, paired with an increase in GSH oxidation to glutathione disulfide (GSSG) [ 48 , 49 , 50 ]. Thus, a decrease in GSH would have been expected in the older, expert pilots, whereas instead, an increment is noted post-flight simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that cellular GSH levels decline with age and in some age-related diseases. [6][7][8] Due to the lack of membrane binding exoenzyme γ-glutamyltranspeptidase (γ-GT) or the presence of an unfavorable concentration gradient between the intracellular and extracellular GSH levels, it is impossible to take up extracellular GSH. γ-GC, as an immediate precursor of GSH, can be readily taken up by many cell types to promote GSH synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…OH' and affect bio-molecules such as carbohydrates, lipids, proteins and nucleic acids [8,9]. It contributes to immune pathologies including cancer, inflammation, diabetes, hypertension, AIDS and aging, etc [10]. Antioxidants have the ability to reduce or inhibit the oxidation of biomolecules such as lipids, proteins, etc.…”
Section: Introductionmentioning
confidence: 99%